Middle leaders and trust: a mixed method study of two private secondary schools in Islamabad in Pakistan - Riaz, Saira (2023)
This is a case study of two private Secondary schools in Islamabad. The focus of school A is profit-based and commercial whereas School B provides quality and values-based education. This study explored the phenomenon of middle management with reference to their leadership roles in schools. Also this enquiry measured the level of relational trust among the principal, middle leaders, teachers and clients (students and parents) from faculty perspective by using the grounded theory of five facets of trust: benevolence, competence, reliability, open communication and honesty. This study is more qualitative in nature. Questionnaire and semi-structured interviews were used as research instruments. The findings revealed that middle leaders practice Transformational leadership and play multifunctional roles such as teachers, coordinators, managers, curriculum developers, mentors, monitors, trainers, event organizers and advisors. Their leadership roles extend to the whole school development. High level of trust was found among middle leaders, teachers and colleagues due to teachers’ participation in planning activities, friendly and fear free work climate, healthy and productive work relations. It was found that school A was multilayered with bureaucratic hierarchy system, power conscious, commercial mind set with low level of trust than School B. In both schools it was found that middle managers were not given autonomy and authority by the principal. Although private schools follow the western model of leadership based on democracy but the traditional elements of delegation, control and uncertainty are still present.